Household Food Security of Cocoa Farmers (Theobroma Cacao L) on Former Coal Mine Land in Sawahlunto City - Faidil Tanjung; Dwi Evaliza; Cyntya Veralina; Mizi Sasrido (Journal of Social Research, 2023)
An overview of the food security vulnerability of cocoa farmer households on former mining lands is able to provide recommendations in efforts to increase the income that can support the welfare of farmer households and increase regional farmer food security. The purpose of this study was to determine the amount of cocoa farmer household income and cocoa farmer household expenditure and the level of food security of cocoa farmer households in ex-mining areas in Talawi District, Sawahlunto City. With a sample of 39 respondents selected by simple random sampling and data analysis using a quantitative approach. This study shows the results that the average household income of respondents is IDR 3,082,821 per month. Whereas for the average respondent household food expenditure is Rp.1,426,282.05 or 59.94% of total household expenditure, the respondent's household non-food expenditure is Rp.953,384.62 or 40.06% of total household expenditure ladder. Judging from the proportion of household expenditure to total expenditure, the results show that the level of household food security is 23.08% of households are food secure and 76.92% of households are food insecure. Households should improve food expenditure patterns by paying attention to and diversifying the amount and type of food they will consume.